Corrosion resistance study of 439L ferritic stainless steel subjected to high temperature variation. Issue 1 (1st January 2021) - Loto, Roland Tolulope
Abstract: Automobile production plants have advanced the utilization of stainless steel alloys for the production of exhaust mufflers due to corrosion failures associated with their operating lifespan and conditions of application. Corrosion vulnerability of as received and heat treated (500oC and 1000oC) 439 L ferritic stainless in 3.5 M H2 SO4 electrolyte at 0% to 6% NaCl concentration was evaluated with potentiodynamic polarization, potentiostatic measurement, open circuit potential measurement, and optical microscopy characterization. Potentiodynamic polarization results show heat treatment improved the general corrosion resistance of the steel. Heat treated 439 L steel at 500°C displayed the lowest corrosion rate trailed by the heat treated steel at 1000°C. However, potentiostatic measurement shows that heat treatment decreases the resistance of the steel to localized corrosion deterioration from inspection of the metastable pitting current and passivation potential values. Results from open circuit potential measurement show heat treatment increases the thermodynamic tendency for 439 L steel to corrosion while improving its corrosion resistance. Optical images of the as-receive and heat treated steels show the presence of numerous corrosion pits and corrosion along the grain boundaries. However, the extent of deterioration is significantly higher for the as-received steel.